Implementasi Fungsi Keimigrasian dalam Keamanan Negara - Muharam, Alfathur; Butar, Paranio Rajata Butar; Wibawanto, Muhammad Rizky Yoga (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The increasing threat of globalization, both traditional and non-traditional, has become a particular concern for the Indonesian government; the rapid and widespread development of the world economy has made policies related to free markets and investment huge. The research method used by the author is a qualitative method with a literature review approach. The author uses secondary data to analyze the results, namely, primary, secondary, and tertiary materials. The results of the study stated that: The Directorate General of Immigration is present as the executor of duties and functions in the field of immigration. The chess of the immigration function is the basis for carrying out the duties and functions carried out by the directorate general of immigration. This writing is intended to explain the process of immigration in the state security sector; immigration has a vital role in maintaining state sovereignty.